IMPLEMENTASI METODE DATA MINING APRIORI PADA APLIKASI PENJUALAN PT. TIGA RAKSA SATRIA - Siti Qomariah; Hanifah Ekawati; Sepriyadi Belareq (Ilmu Komputer, FMIPA, Universitas Pakuan, 2020)
PT. Tiga Raksa Satria, Tbk is a company engaged in trading in the form of selling products of various brands to shops in Samarinda. the recording process of selling has been done computerized, but the sales data has not been processed optimally. there is no application that analyzes sales data for category, planning and service to consumers. Analyzing sales data is an important part of the company, an analysis of sales results has an impact on the profits to be gained by the company. Datamining is the science of digging up valuable information and knowledge in databases. One algorithm in data mining is a priori algorithm. Datamining is widely implemented in various fields such as business, commerce, and others. This research aims to make an application with the Application of Data Mining Basketball Analysis Method with Apriori Algorithm to process the sales data in a more structured, detailed and know the problems in product sales. This application generates rules that help draw conclusions needed for drawing conclusions of strategic information for companies regarding sales data. Application made with the application of a priori methods helps in the analysis of sales data that is owned.